To Evaluate the Efficacy of Gunjaphaladi Lepam and Vibhitakadi Kwatha in Management of Switra w.s.r to Vitiligo (AYUSHDHARA, 2023)
Switra is type of Kushta roga often encountered by Ayurvedic pediatric OPDs characterized by Twak swetata (white discolouration of skin). it is caused due to involvement of Tridoshas and Dhatus like Rasa, Rakta, Mamsa, Meda. Based on the symptoms Switra can be correlated with vitiligo in modern science. Vitiligo is a common pigmentary disorder of great socio-medical importance. Vitilogo is an acquired macular depigmentation disorder associated with the destruction of melanocytes. It affects approximately 0.5-2% of world population.In children Shamana is preferred than Shodhana therapy. So, a clinical study aimed to evaluate the efficacy of Gunjaphaladi lepam and Vibhitakadi kwatha in Switra in children 6-16 years of age was conducted considering inclusive and exclusive criteria. Patients were given Gunjaphaladi lepam for external application and Vibhitakadi kwatha internally for 60 days and called for follow up after 30 days of completion of treatment. Among 30 patients, maximum patients were having mild improvement i.e., 56.66%, 17% showed complete remission and 13.33% showed moderate improvement. The clinical study clearly concludes that Gunjaphaladi lepam and Vibhitakadi Kwatham are safe and effective in the management of Switra in children.